Urgensi literasi informasi pada mahasiswa Universitas Hayam Wuruk Perbanas - Ramadhani, Aditya; Reza Rurah; Purwandini, Dyana (Jurnal FPPTI, 2023)
Information literacy is a person's ability to search, find, analyze, evaluate, and disseminate information again to meet the information needs used in solving problems. Libraries and librarians are essential in introducing and providing academic information literacy skills. Based on a series of activities and part of the Learning Information Resources Services (LERES) service carried out by the library and librarians of the University of Hayam Wuruk Perbanas using the user education method for new Diploma, Undergraduate and Postgraduate students, the English Self Access Center (ESAC) makes videos according to the theme and retelling the contents of the film screening in English, reference tools manager services such as Mendeley and Vos Viewer, training on scientific information search methods, as well as dissemination of self-uploading thesis. The purpose of these services is for students to think critically and logically, use information, and solve problems faced in the education and community environments. The results of the LERES service show that all activity students attend run smoothly, and students are enthusiastic to participate in a series of activities. It is hoped that after this series of activities, students will be ready and able to go directly into the community with the provision of information literacy skills.